2017
DOI: 10.1111/ijfs.13610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peptide–phenolic interaction on the antioxidant capacity of walnut protein hydrolysates

Abstract: Summary Walnut antioxidant peptides and phenolic compounds (POHs) commonly coexist in walnut protein hydrolysates (WPHs). However, the peptide–phenolic interaction and its effects on antioxidant activities of WPHs remain unknown. Fluorescence and dynamic light scattering were used to study the peptide–phenolic interaction in WPH‐POH mixtures (W‐P) with different POH/WPH ratios; antioxidant abilities of POH only solution, WPH only solution and W‐P were measured with three assays: DPPH radical scavenging, Fe2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The λ max of SPI/SPIHs had a slight red shift from 333.5 to 336 nm (SPI), 344.5 to 346.5 nm (SPIH1), 344 to 346 nm (SPIH2), and 345.5 to 347 nm (SPIH3) after interacting with C3G, indicating that tryptophan and tyrosine residues were in a more hydrophilic environment. These results are similar to those obtained in some related studies [ 16 , 24 ]. The K SV , K q values of SPI/SPIHs with C3G are presented in Table 2 to illustrate the fluorescence quenching mechanism.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The λ max of SPI/SPIHs had a slight red shift from 333.5 to 336 nm (SPI), 344.5 to 346.5 nm (SPIH1), 344 to 346 nm (SPIH2), and 345.5 to 347 nm (SPIH3) after interacting with C3G, indicating that tryptophan and tyrosine residues were in a more hydrophilic environment. These results are similar to those obtained in some related studies [ 16 , 24 ]. The K SV , K q values of SPI/SPIHs with C3G are presented in Table 2 to illustrate the fluorescence quenching mechanism.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the binding sites between ANS and the hydrophobic groups on the protein surface decreased due to the binding of hydrophobic groups to C3G through hydrophobic interactions [ 5 , 21 ]. Su et al [ 16 ] also observed that as the phenolic compounds/walnut protein hydrolysates ratio ( w / w ) increased from 1:600 to 1:120, the fluorescence intensity of ANS almost decreased linearly, indicating a surface hydrophobicity reduction in their complexes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations